The Impact of Swirls on Slurry Flows in Horizontal Pipelines - Hongbo Shi (MDPI AG, 2021)
In deep ocean transportation pipeline, the swirling internal flow has a significant impact on the marine minerals transportation efficiency and safety. Therefore, the present work investigates various swirl flow motions for the slurry transport characteristics of the multi-sized particulate flow in a horizontal pipeline. Since the internal flow is a liquid-solid-solid mixture, a steady-state three-dimensional Eulerian-Eulerian multiphase approach in conjunction with the k-<semantics>ω</semantics> SST turbulence model is implemented for numerical simulation in the commercial CFD software ANSYS FLUENT 17.0. Numerical predictions of the mixture solid concentration distributions are generally in good conformance with experimental measurements. It is clearly revealed the transition of flow regime from heterogeneous to pseudo-homogeneous with the increasing level of swirl intensity at inlet. Compared to non-swirling flow, the swirling flow is of benefit to the multi-sized solid suspension capacity and the transportation efficiency. Moreover, the intense swirling vortex results in a strong influence on the characteristics of the lubrication layer formed by fine solid particles near the bottom of the pipe. These results provide valuable insights regarding the influence of swirl flow on the transport process for deep ocean mining.